2019
DOI: 10.3390/nu11051176
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Tolerance Test and Pharmacokinetic Study of Kaempferia parviflora Extract in Healthy Subjects

Abstract: Kaempferia parviflora Wall. ex Baker (KP), Krachaidam in Thai or Thai ginseng, is a herbal medicine that has many potential pharmacological effects. The effect of KP extract on blood glucose level in rodent was reported. This study focused on the oral glucose tolerance test and pharmacokinetic study in healthy volunteers administered with KP extract (90 and 180 mg/day, placebo). The oral glucose tolerance tests were performed at baselines and 28-days of administration. The pharmacokinetics were determined afte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Furthermore, as shown in table 3, the consumption of capsules from the first day for each participant significantly dropped after taking 400 mg capsules. The results that show the reduction of blood glucose using KP was consistent with results that have been reported by Azuma and Sripanidkulchai [17,18].…”
Section: Study On Blood Glucose Levelsupporting
confidence: 92%
“…Furthermore, as shown in table 3, the consumption of capsules from the first day for each participant significantly dropped after taking 400 mg capsules. The results that show the reduction of blood glucose using KP was consistent with results that have been reported by Azuma and Sripanidkulchai [17,18].…”
Section: Study On Blood Glucose Levelsupporting
confidence: 92%
“…The ethanol extract of K. galanga found to be beneficial to combat an obesity-induced dermatopathy system in Tsumura Suzuki obese diabetic (TSOD) mice as a model of obesity. It was shown a decrease in the body weight of rats and the thickness of the subcutaneous fat layer more than the polymethoxiflavonoid fraction, which was utilized as a dietary supplement in controlling skin disorders due to obesity (61).…”
Section: Anti-obesity Activitymentioning
confidence: 99%
“…A subsequent study by Sripanidkulchai et al 18 reported the oral pharmacokinetics of compound 9 in rats administered Kaempferia parviflora extract, of which compound 9 was a major component. Recently, a clinical trial by the same group 19 further evaluated the oral pharmacokinetics and metabolites of compound 9 after administration of K. parviflora extract. Despite their extensive work and positive findings, K. parviflora extract contains a large number of constituents in addition to compound 9, and the pharmacokinetics of compound 9 were likely to be influenced by other components because of potential competition or inhibition between components during the pharmacokinetic process (e.g., absorption and metabolism).…”
Section: ■ Introductionmentioning
confidence: 99%
“…A subsequent study by Sripanidkulchai et al reported the oral pharmacokinetics of compound 9 in rats administered Kaempferia parviflora extract, of which compound 9 was a major component. Recently, a clinical trial by the same group further evaluated the oral pharmacokinetics and metabolites of compound 9 after administration of K. parviflora extract.…”
Section: Introductionmentioning
confidence: 99%